IMPLEMENTASI SPK UNTUK MENENTUKAN PENERIMAAN KARYAWANBARU DI PT. WIRYAMANTA SADINA MENGGUNAKAN METODE SAW BERBASIS WEBSITE - Cahya Radita, Jovan; Suwarno, Joko (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2025)
The recruitment and selection process is a strategic stage in human resource management, especially for PT. Wiryamanta Sadina, a company engaged in the Food and Beverage industry. The company’s manual selection process often faces challenges such as subjectivity, inconsistent evaluations, and suboptimal data management. This study aims to develop a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to assist in conducting employee selection more objectively and systematically. The SAW method is applied to evaluate candidates based on criteria such as education, work experience, location range, employment status, and age, with weight values assigned according to their level of importance. The system is designed as a web application to facilitate applicant data management, initial screening, and automatic ranking presentation. The results show that the system can reduce subjectivity in assessment, improve selection efficiency, and produce candidate rankings aligned with the company’s needs. Thus, the implementation of a web-based DSS using the SAW method can serve as an effective solution to support the recruitment process at PT. Wiryamanta Sadina.